Distinguish Thyroid Malignant from Benign Alterations using Trace Element Contents in Nodular Tissue determined by Neutron Activation and Inductively Coupled Plasma Mass Spectrometry - Vladimir Zaichick (Journal of Clinical and Diagnostic Pathology, 2022)
Background Thyroid benign (TBN) and malignant (TMN) nodules are a common thyroid lesion. The differentiation of TMN often remains a clinical challenge and further improvements of TMN diagnostic accuracy are warranted. The aim of present study was to evaluate possibilities of using differences in trace elements (TEs) contents in nodular tissue for diagnosis of thyroid malignancy. Methods Contents of TEs such as silver (Ag), aluminum (Al), boron (B),, beryllium (Be), bismuth (Bi), cadmium (Cd), cerium (Ce), cobalt (Co), chromium (Cr), cesium (Cs), iron (Fe), gallium (Ga), mercury (Hg), iodine (I), lanthanum (La), lithium (Li), manganese (Mn), molybdenum (Mo), neodymium (Nd), nickel (Ni), lead (Pb), praseodymium (Pr), rubidium (Rb), antimony (Sb), scandium (Sc), selenium (Se), samarium (Sm), tin (Sn), thallium (Tl), uranium (U), yttrium (Y), and zinc (Zn) were prospectively evaluated in nodular tissue of thyroids with TBN (79 patients) and to TMN (41 patients). Measurements were performed using a combination of non-destructive instrumental neutron activation analysis with high resolution spectrometry of short- and long-lived radionuclides (INAA-SLR and INAA-LLR, respectively) and destructive method such as inductively coupled plasma mass spectrometry (ICP-MS). Results It was observed that in TMN tissue the mean mass fractions of Be, Fe, I, Sc, and Se are approximately 1.9, 1.7, 14, 3.1, and 1.6 times, respectively, lower while the mass fraction of Ga, Mo, and Rb 62%, 51%, and 33%, respectively, higher than those in TBN tissue. Contents of Ag, Al, B, Bi, Cd, Ce, Co, Cr, Cs, Hg, La, Li, Mn, Nd, Ni, Pb, Pr, Sb, Sm, Sn, Tl, U, Y, and Zn found in the TBN and TMN groups of nodular tissue samples were similar. Conclusions It was proposed to use the I mass fraction, as well as I/Ga, I/Mo, and I/Rb mass fraction ratios in a needle-biopsy of thyroid nodules as a potential tool to diagnose thyroid malignancy. Further studies on larger number of samples are required to confirm our findings and proposals.
Keywords: Thyroid